(untitled) (Al-Academy, 2025)
Children’s theater is one of the arts that relies on the beautiful word and the elegant style of communicating with the child and entering his private world. It is in itself a system of moral and educational values and principles that contribute to his upbringing. Therefore, children’s theater has kept pace with this development that it has witnessed in terms of its construction and has maintained its authentic Arabic character that... Uniqueness with it. The reason for choosing this topic is: because the text of children’s theater is a topic that deserves study as it is a necessary foundation and basic support in that it enables the child to acquire linguistic ability, develop his mind, build his personality, entertain himself, and make him an effective member of society. Therefore, the theatrical text affects the child’s psyche if its concepts are applied in reality. The research consisted of an introduction through which the researcher emphasized the necessity of adopting contemporary visions in the structure of societies by paying attention to children’s literature as a basic pillar of society and the child himself. The first chapter (methodological framework) included the research problem by creating representations different from the hero’s personality in children’s theater by employing positive ideas and different artistic treatments. Accordingly, the research problem was formulated with the following question: What are the representations of the hero’s personality and their role in influencing the child? The chapter included the importance of research: it is an important means of enlightening children about the problems of their society and ways to overcome them. Also, the importance of the research that emphasized knowing the representations of the hero’s personality in children’s theater texts. The research included objective, spatial, and temporal limits, while the second chapter included (the theoretical framework), which consisted of three sections: The first section/the concept of the hero’s personality. The second topic/representations in children’s theater texts. The third topic: The effectiveness of the theatrical text directed at the child and its impact on building his personality. Then come up with indicators of the theoretical framework. As for the third chapter (research procedures), the study population and research sample included the theatrical text directed to children (Tair Al-Saad), written by: Qasim Muhammad. Then comes the fourth chapter (results and conclusions). The researcher also identified paragraphs of recommendations that are related to the results of the study. After that, the researcher suggested two studies that could be adopted by other researchers. Then the study concluded with the references and sources that were adopted in this study